Market power in California's water market - Françeska Tomori; Erik Ansink; Harold Houba; Nick Hagerty; Charles Bos (Tinbergen Institute, 2021)
We estimate market power in California's thin water market. Market frictions may distort the potential welfare gains from water marketing. We use a Nash-Cournot model and derive a closed-form solution for the extent of market power in a typical water market setting. We then use this solution to estimate market power in a newly assembled dataset on California's water economy. We show that, under the assumptions of the Cournot model, market power in this thin market is limited.
Keywords: C72; D43; Q25; 330; Water markets; Market power; California; Cournot-Nash